Variants in Lrrk2 and Snca deficiency do not alter the course of primary encephalitis due to neurotropic reovirus T3D in newborn mice - Michaela O. Lunn; Christopher Rousso; Julianna J. Tomlinson; Earl G. Brown; Michael G. Schlossmacher (PLoS ONE, 2025)
Variants at the leucine-rich repeat kinase-2 (LRRK2) and α-synuclein (SNCA) loci are associated with Parkinson’s disease (PD) risk. Viral infections have also been linked to increased risk of developing PD. In exploring a role for each of the encoded proteins in host response against brain-directed viral infections, we previously demonstrated that two Lrrk2 knock-in variants as well as Snca expression altered survival rates from viral encephalitis following intranasal inoculation of newborn mice with a double-stranded RNA virus: respiratory-enteric-orphan virus, serotype-3 strain Dearing (reovirus T3D). Here, we examined whether outcomes of direct inoculation of the brain by reovirus T3D, which invariably causes lethal encephalitis within 15 days, would also be modified by variants in Lrrk2 and Snca. When we inoculated newborn mice intracerebrally with reovirus T3D, we found that compared to wild-type littermates Lrrk2 p.G2019S kinase-hyperactive and p.D1994S kinase-inactive mutant mice did not show any significant difference in time-to-death or in viral titres in the brain, and revealed no sex difference. In parallel studies, the reduction or absence of endogenous α-synuclein did not alter the course of disease in reovirus T3D-infected mice. Together, these findings suggest that while variants in the PD-linked Lrrk2 and Snca genes influenced disease outcomes of intranasally acquired reovirus T3D encephalitis, they did not affect survival outcomes in the intracerebrally acquired reovirus T3D encephalitis model.